Rules in information sharing for security. (April 2022) - Chan, Janet; Logan, Sarah; Bennett Moses, Lyria
Information sharing has become a central concern for security agencies since 9/11. Previous research has identified a number of barriers to information sharing among agencies: a combination of legal or policy constraints, interagency rivalry and mistrust, and technology. Drawing on ideas from the sociology of information and trust, this article conceptualises the sharing/withholding of information between agencies as dependent on rules as a system of trust. Adapting Richard Ericson's framework of the different contexts of rule-following and making use of an Australian case study, the article demonstrates how law, culture and technology are intertwined in constraining or enabling access to information. The implications of this model for legal and policy interventions are discussed.